Planning implementation of method of observation in social sciences - Vladimir Ilić (University of Belgrade, 2016)
The paper deals with the problems while planning the application of method of observation as the primary method for data collection. These include determining the objectives, theoretical and operational elaboration of the research plan and collection of initial evidence from other sources of data that can be used to successfully plan research mainly based on observation. In the first section of the paper it is pointed to the unjustified overemphasis of differences between participatory and non-participatory forms of observation in its planning. The second section shows the possibility of its application to other sources and methods of data collection when planning observations. Special attention is paid to the role of interview and sequential analysis. In the third section, the issues of preparing data analysis in the planning of observation are specifically discussed. The fourth section shows the specificity of the planning of observation, depending on the nature of the data. We also considered the concretization of the plan of observation, including the selection of size, location and time for performing monitoring and positioning one or more observers. The fifth section briefly points to some suggestions about training observers. The concluding section of the paper deals with planning during the observations, with emphasis on grounded theory.